Use of hydroxychloroquine for novel corona virus infection in India: is it ethically justifiable? - Verma, Ramesh; Chayal, Vinod; Kalhan, Meenakshi; Dhaka, Rohit; Agrawal, Ginni; Jain, Piyush; Singh, Tarun (International Journal Of Community Medicine And Public Health, 2020)
Coronavirus disease is caused by a novel virus belonging to the family of corona viruses similar to severe acute respiratory syndrome (SARS) and name given to the novel virus as SARS Coronavirus- 2 (SARS-CoV-2) and the disease was named as COVID-19 on 11th February 2020 by World Health Organization (WHO). First case of this infection was reported in December 2019 in Wuhan city of China and after that it spread globally.3 On 30th January 2020, WHO declared this disease as Public Health Emergency of International Concern (PHEIC) and on 11th March 2020, WHO declared it as a pandemic when the infection was reported from all six WHO regions.